The Effects of Fiscal Policy on Macroeconomic Activities: Evidence from Iran - Naser Khiabani; mahbubeh delfan (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2017)
This study investigates how fiscal policy shocks affect macroeconomic activities in an oil exporting economy using a real business cycle model (RBC). We make distinction between public sector of economy from private sector and evaluate the effect of public crowded- (in or out) effect on private sector. Our findings indicate that in Iran, a positive fiscal expansion- a positive consumption expenditure shock- does not have a positive, sizeable and permanent effect on the investment, employment and production of private sector. On the other hand, the results show that the shock has a negative effect on private sector consumption expenditure. This result is consistent with the Ricardian equivalence theorem, suggesting that a government cannot stimulate spending since people assume that whatever is gained now will be offset by higher taxes in the future.